Design and analysis of strut-based lattice structure cranial implant - M.Z. Khan; J. Bhaskar; A. Kumar (Journal of Mechanical Engineering and Sciences, 2023)
A specialized medical cranioplasty procedure entails the use of implants of various materials, forms, and sizes. Computational technologies such as modelling and simulation, have refined the technique for creating these implants catering to patient specific needs. Superior qualities of lattice structures have considerable usage in implants. This study mainly focuses on three distinct types of strut-based lattice structures, Octet, Diamond, and Kelvin, for constructing cranial implant models using CAD tools like Solidworks and nTopology. Titanium alloy (Ti6Al4V) is used to test the behaviour of the designed implants in two cases: impact of external force and increase in intracranial pressure. Level of porosity is compared to determine extent of porosity of these implants, as porosity is significant in osseointegration. According to the study, these lattice structures give satisfactory results and can be utilized to make the implant more porous while satisfying the load bearing capacity.